2019
DOI: 10.1111/liv.14098
|View full text |Cite
|
Sign up to set email alerts
|

The tumour microenvironment and immune milieu of cholangiocarcinoma

Abstract: Tumour microenvironment is a complex, multicellular functional compartment that, particularly when assembled as an abundant desmoplastic reaction, may profoundly affect the proliferative and invasive abilities of epithelial cancer cells. Tumour microenvironment comprises not only stromal cells, mainly cancer‐associated fibroblasts, but also immune cells of both the innate and adaptive system (tumour‐associated macrophages, neutrophils, natural killer cells, and T and B lymphocytes), and endothelial cells. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 155 publications
(363 reference statements)
2
131
0
2
Order By: Relevance
“…94 CCA tumors are often accompanied with the tumor microenvironment in dense stromal tissues containing fibroblasts and lymphocytes promoting CCA progression. 95 Melatonin inhibited lymphocyte infiltration such as Th17 + cells and decreased inflammatory responses including expression of IL-1β and NF-κB in hamsters with fluke infestation and NDMA treatment. 96 Although further evidence is required, melatonin administration may be used for CCA to inhibit tumor growth and regulate functions of CCA microenvironment.…”
Section: Cholangiocarcinomamentioning
confidence: 93%
See 1 more Smart Citation
“…94 CCA tumors are often accompanied with the tumor microenvironment in dense stromal tissues containing fibroblasts and lymphocytes promoting CCA progression. 95 Melatonin inhibited lymphocyte infiltration such as Th17 + cells and decreased inflammatory responses including expression of IL-1β and NF-κB in hamsters with fluke infestation and NDMA treatment. 96 Although further evidence is required, melatonin administration may be used for CCA to inhibit tumor growth and regulate functions of CCA microenvironment.…”
Section: Cholangiocarcinomamentioning
confidence: 93%
“…O viverrini infection plus carcinogen N ‐nitrosodimethylamine (NDMA) administration developed CCA in hamsters, and melatonin administration (10 or 50 mg/kg, daily for 120 days, orally) elevated Bcl‐2 expression and decreased BAX expression resulting in attenuated CCA development and improved survival rates in this model . CCA tumors are often accompanied with the tumor microenvironment in dense stromal tissues containing fibroblasts and lymphocytes promoting CCA progression . Melatonin inhibited lymphocyte infiltration such as Th17 + cells and decreased inflammatory responses including expression of IL‐1β and NF‐κB in hamsters with fluke infestation and NDMA treatment .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…It is increasingly evident that the CCA desmoplastic microenvironment plays an important role in cancer cell development, and strategies targeting the tumour stroma in combination with the CCA cancer cell will present new diagnostic and therapeutic perspectives. 114 Due to the rarity of this tumour, initiatives are necessary to develop international consortia such as the Thailand Initiative in Genomics and Expression Research for Liver Cancer (TIGER-LC), the European Network for the Study of Cholangiocarcinoma (ENS-CCA), the International Cholangiocarcinoma Research Network, along with patient advocacy groups like the Cholangiocarcinoma Foundation, to enable the creation of international translational and clinical research collaborations that can perform multicentre clinical trials with the aim of elucidating new therapies.…”
Section: Lt For Hccamentioning
confidence: 99%
“…Checkpoint inhibitor-based immunotherapy have achieved notable success in the clinical treatment of tumor [13][14][15][16][17]. Although many studies have demonstrated that immunotherapy shows a promising safety and e cacy for patients with CCA, the response rate is disappointing [18][19][20][21]. Tumor immune microenvironment (TIME) composed of immune in ltrating cells plays an important role in tumor progression and immunotherapeutic response [22][23][24].…”
Section: Introductionmentioning
confidence: 99%